Exploring the immune profile in a TNBC mouse model while elucidating the cytosolic EZH2 expression in cancer stem cells - Khalilatul Hanisah Binte Mohd Kahliab (Nanyang Technological University, 2023)
In a previous study in our lab, we found that the expression of exogenous EZH2 in the cytosol contributes to colony formation in H16N2 cell lines, and increased tumour growth in both immune-deficient and immune-competent mouse models. Therefore, we hypothesised that cancer stem cells from TNBC tumours should have increased cytosolic EZH2 due to the aggressiveness of this cancer compared to the different breast cancer subtypes. To investigate if this phenomenon is true, we employed a BLG-Cre; Brca1F22–24; p53 KO mouse model to investigate cytosolic EZH2 expression in TNBC tumours. Indeed, upon enriching YFP+ BRCA1-deficient cancer cells from our TNBC tumours, we observed the YFP+ CD44+ BRCA1-deficient cancer cells exhibited increased cytosolic EZH2 compared to YFP+ CD44– BRCA1-deficient cancer cells. We also monitored the immune cell changes in the blood of LGB-Cre+p53+/–Brca1fl/fl YFP/YFP mice to predict cancer progression and tumour formation since spontaneous TNBC tumours require extended incubation times to develop. Upon monitoring the immune cell changes in the blood at different time points, we observed immune cells change over time from a pro-inflammatory to an anti-inflammatory phenotype to promote tumorigenesis.